Property-type diversification strategies and their performance implications on the South African real estate investment trusts - Bantseke, Thathatso (My University, 2018)
Background - Extensive research that examines the performance implications of regional and property-type diversification has been undertaken in Asia, United States of America and the United Kingdom. Research on South African real estate investment trusts’ (SAREITs) diversification strategies is insufficient. The South listed property market is ranked amongst the largest sectors on the JSE with 35 SA REITs listed on the JSE, which represent a market capitalisation of over ZAR435 billion which is 6% of the JSE All Share Index market value. The size of this sector emphasizes the importance it within the South African economy. This study is of significance to the academic fraternity as well as local and international investors and asset managers who are interested in participating in the South African REITs market Purpose -The study investigates the effects of property-type diversification on SAREITs performance through literature review which explores the key variables in the diversification and performance relationship to create an understanding of the REITs sector. Correlation and multiple regression analysis is undertaken utilizing secondary data from Published Annual Financial Statements, MSCI South Africa and INET BFA Databases. The REITS analyzed have the majority of their underlying property assets located within South Africa and have been listed on the JSE for the 2014 to 2017 financial years. Findings - The findings from the literature review highlight that property type diversification strategies although playing a paramount role in portfolio formation of REITs and performance, the returns of companies are also influenced by other moderating factors such as property specific, organizational and industry characteristics. Regressions between return variables with the property types and degree of diversification of REITs, show both positive and negative relationship but these associations were found to be statistically insignificant. The hypothesis is not fully supported by the statistical data analysis and entails that other non-systemic risk factors such as“firm leverage policies”;“management style”;“net asset values”;“size of REITs stock” and “property location” need to be analysed in conjunction with in order to yield more robust results. Limitations - The study focused on SAREITS with the majority of their underlying property assets located within South Africa and listed on the JSE for the 2014 to 2017 financial years. Complete regional data on the listed REITs was lacking which restricted the study to an analysis of property type strategies. Utilisation of secondary data restricted the research to a single set of data and this impacts on the findings as some of the data is incomplete. Further studies in this area could include regional-type diversification strategies analysis over a longer observation period.
A research report submitted in partial fulfillment of the requirements for a Master of Science degree in Building to the University of the Witwatersrand, Faculty of Engineering and the Built Environment, School of Construction Economics and Management March 2018
Keywords: Real estate investment--South Africa; Real property--South Africa; Real estate business--South Africa--Finance